Accuracy of Individualized Custom Tibial Cutting Guides in UKA. Issue 3 (October 2014) - Heyse, Thomas J.; Lipman, Joseph D.; Imhauser, Carl W.; Tucker, Scott M.; Rajak, Yogesh; Westrich, Geoffrey H.
Background: Component malposition is one of the major reasons for early failure of unicompartmental knee arthroplasty (UKA). Questions/Purposes: It was investigated how reproducibly patient-specific instrumentation (PSI) achieved preoperatively planned placement of the tibial component in UKA specifically assessing coronal alignment, slope and flexion of the components and axial rotation. Patients and Methods: Based on computer tomography models of ten cadaver legs, PSI jigs were generated to guide cuts perpendicular to the tibial axis in the coronal and sagittal planes and in neutral axial rotation. Deviation ≥3° from the designed orientation in a postoperative CT was defined as outside the range of acceptable alignment. Results: Mean coronal alignment was 0.4 ± 3.2° varus with two outliers. Mean slope was 2.8 ± 3.9° with six components in excessive flexion. It was noted that the implants were put in a mean of 1.7 ± 8.0° of external rotation with seven outliers Conclusions: PSI helped achieve the planned coronal orientation of the component. The guides were less accurate in setting optimal tray rotation and slope.